Comparison of Somatic and Sudomotor Nerve Fibers in Type 2 Diabetes Mellitus - Sohn, Eun-Hee; Song, Kyu-Sang; Lee, Ju Yeon; Lee, Ae Young (Journal of clinical neurology (Seoul, Korea), 2017)
The objective of this study was to find a sensitive method for the early detection of diabetic polyneuropathy (DPN) and determine the relationship between the functions of somatic and autonomic small nerve fibers in DPN. Patients with type 2 diabetes mellitus and DPN based on clinical symptoms, signs, intraepidermal nerve fiber density (IENFD), and findings in the quantitative sudomotor axon reflex test (QSART) were enrolled retrospectively. Neurological examinations and nerve conduction studies were performed on all patients. Heart-rate variability during deep breathing (DB ratio) and the Valsalva maneuver (Valsalva ratio) were used to quantify the cardiovagal function. Patients were divided into two groups: 1) normal nerve conduction, defined as small-fiber neuropathy (SFN) and 2) abnormal nerve conduction, defined as mixed-fiber neuropathy. In total, 82 patients were enrolled (age: 60.7±10.7 years, mean±SD). A decreased IENFD was the most frequent abnormality across all of the patients, followed by abnormalities of the QSART and cardiovagal function. A decreased IENFD was more sensitive than the QSART, DB ratio, and Valsalva ratio for detecting diabetic SFN. The DB ratio was significantly correlated with the duration of diabetes mellitus and clinical symptoms and signs. There was no correlation between the IENFD and the findings of the QSART for the distal leg. Measuring the IENFD was a more sensitive method than the QSART for the early detection of DPN. The degree of involvement of the somatic small nerve fibers and sudomotor nerve fibers was independent in DPN.